Digital Literacy Dan Cyber Socialization In The Context Of 21st Century Education: A Systematic Review - Fajri, Siti Rabiatul; Fajri, Nurul; Sarnita, Fitria; Fitriani, Herdiyana; Bago, Adam Smith; Kerti Nitiasih, Putu; Nancy Riastini, Putu; I Gede Wawan Sudatha (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
This research provides an in-depth review of the integration of digital literacy and cyber socialization in 21st-century education, positing the importance of these two aspects in preparing students for an ever-evolving world. Using PRISMA's framework for systematic analysis, the study evaluated articles from reputable journals between 2014 and 2024, presenting results that underscore a significant shift in the educational paradigm from traditional to digital. Digital literacy, defined as the ability to use technology efficiently, search and evaluate information, and communicate effectively on digital platforms, has become an essential requirement in modern education. The study shows that digital literacy not only improves technical skills but also supports critical and creative learning among students. In addition, digital literacy education includes teaching ethics and online safety and encouraging responsible internet use. Cyber socialization, with its focus on interaction through social media and digital platforms, has enriched the learning experience through wider collaboration and exchange of resources. However, it also poses challenges such as cyberbullying and security issues, which demand a structured educational response to address related social and psychological issues. The Industrial Revolution 4.0 and the COVID-19 pandemic have accelerated the acceptance of technology in education, emphasizing the importance of character education and the adaptation of innovative teaching methods. Education that is responsive to technological change must integrate digital literacy into all aspects of learning, leading to a more holistic and inclusive approach. Overall, the study underscores the importance of digital literacy and cyber socialization in shaping adaptive and supportive learning environments. 21st-century education must recognize and utilize technology not only as an auxiliary tool but as an integral part of the curriculum, to equip students with the skills needed to succeed in the digital age. By ensuring that digital literacy and cyber socialization are at the heart of education, we can anticipate future needs and challenges, shaping a generation that can not only survive but thrive in an ever-changing digital landscape.